2008
DOI: 10.1021/je8005612
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Equilibrium Conditions for Tetra-n-butyl Ammonium Bromide

Abstract: Hydrate equilibrium conditions for tetra-n-butyl ammonium bromide (TBAB) aqueous solutions were experimentally studied and reported in the mole fraction from 0.003 to 0.047 and the temperature range of (276.35 to 285.65) K at atmospheric pressure. The phase change temperature of TBAB hydrate increases with the increase of the concentration of TBAB aqueous solution when the mole fraction of TBAB aqueous solution is less than 0.044.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…TBAB semiclathrate hydrate has potential as a cold storage material for air conditioning 6,8,11,12 as well as a thermodynamic hydrate promoter of hydrogen storage, 9,13−18 gas absorption, 18−22 and gas separation. 18,19,23−27 In the case of the TBAB mixed semiclathrate hydrates enclathrating hydrogen (H 2 ), 15 krypton (Kr), 22 or xenon (Xe), 20 it has been reported that the structural phase transition occurs at high pressures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBAB semiclathrate hydrate has potential as a cold storage material for air conditioning 6,8,11,12 as well as a thermodynamic hydrate promoter of hydrogen storage, 9,13−18 gas absorption, 18−22 and gas separation. 18,19,23−27 In the case of the TBAB mixed semiclathrate hydrates enclathrating hydrogen (H 2 ), 15 krypton (Kr), 22 or xenon (Xe), 20 it has been reported that the structural phase transition occurs at high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…TBAB semiclathrate hydrate has potential as a cold storage material for air conditioning ,,, as well as a thermodynamic hydrate promoter of hydrogen storage, ,− gas absorption, and gas separation. ,, In the case of the TBAB mixed semiclathrate hydrates enclathrating hydrogen (H 2 ), krypton (Kr), or xenon (Xe), it has been reported that the structural phase transition occurs at high pressures. Also in the argon + TBAB mixed semiclathrate hydrate system, the phase behavior implies the existence of the structural phase transition, although the authors did not state it .…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary ammonium salts (QASs), such as tetrabutylammonium bromide (TBAB) and tetrabutylammonium chloride (TBAC), , are SCH formers and could form SCHs with water molecules. The structure of these SCHs is characterized by the polyhedral water–anion host lattice, built by water molecules together with halide anions through hydrogen bonding, encaging the butyl groups in large cages and typically leaving small dodecahedral cages (5) vacant to store or capture small gas molecules. Presently, many studies focusing on the thermodynamic stability of SCHs at ambient pressure have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Semiclathrate hydrate formers comprise of a large number of ammonium salts, phosphonium salts, sulfonium salts, and amines. Tetrabutlyammonium bromide (TBAB), tetrabutylammonium chloride (TBAC), tetrabutylammonium fluoride (TBAF), tetrabutylphosphonium bromide (TBPB), and tetrabutylphosphonium chloride (TBPC) , are widely used for semiclathrate hydrate formation. Semiclathrate hydrate, similar to clathrate hydrates, possesses many of the physical and structural properties as common clathrate hydrate, while it has particular features.…”
Section: Introductionmentioning
confidence: 99%